PENGARUH KETERLIBATAN KERJA, PENGAWASAN DAN KARAKTERISTIK PEKERJAAN TERHADAP KINERJA PEGAWAI PADA KANTOR UNIT PENYELENGGARA PELABUHAN KELAS I MOLAWE - Syamsir, Syamsir; Razak, Abdul; Yunus, Asraf (JIDE : Journal Of International Development Economics, 2024)
This study aims to determine and analyze the influence of job involvement, supervision, and job characteristics on employee performance at the Office of Class I Port Operator Unit in Molawe. The sample in this study consists of all employees at the Office of Class I Port Operator Unit in Molawe, totaling 54 individuals. This study uses multiple linear regression analysis. The results of the study show that: (1) Job involvement, supervision, and job characteristics have a positive and significant effect on employee performance at the Office of Class I Port Operator Unit in Molawe. (2) Job involvement has a positive and significant effect on employee performance at the Office of Class I Port Operator Unit in Molawe. (3) Supervision has a positive and significant effect on employee performance at the Office of Class I Port Operator Unit in Molawe. (4) Job characteristics have a positive and significant effect on employee performance at the Office of Class I Port Operator Unit in Molawe.